2018
DOI: 10.1177/0361198118783152
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Risk of Wrong-Way Driving Entry at the Exit Ramp Terminals of Full Diamond Interchanges

Abstract: Wrong-way driving (WWD) crashes are a critical safety issue on freeways. Although these crashes are rare and random in nature, they often result in severe injuries and/or fatalities. Typically, exit ramp terminals are the initial point of entry for wrong-way (WW) drivers on freeways. Therefore, it is important for transportation agencies to identify the exit ramp terminals with higher possibility of WW entries and apply safety countermeasures to reduce the chances of their occurrence. However, the random natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Such use of WW signs close to exit ramp terminals can be associated with clear visibility and less likelihood of causing driver confusion. The authors' previous work reported that the probability of WWD increases by approximately 4.5 times when the distance of the first WW sign is more 200 ft from the crossroad (10,11).…”
Section: Signs Pavement Markings and Traffic Signalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Such use of WW signs close to exit ramp terminals can be associated with clear visibility and less likelihood of causing driver confusion. The authors' previous work reported that the probability of WWD increases by approximately 4.5 times when the distance of the first WW sign is more 200 ft from the crossroad (10,11).…”
Section: Signs Pavement Markings and Traffic Signalsmentioning
confidence: 99%
“…Previous studies reported numerous safety countermeasures to reduce the chances of WW entry at the exit ramp terminals of freeway interchanges. Collectively, these safety countermeasures can be divided into three categories: (a) geometric design features (6)(7)(8)(9)(10)(11); (b) application of TCDs (7,(10)(11)(12)(13)(14); and (c) application of intelligent transportation systems. Based on the focus of this study, the following paragraphs discuss the recommended guidelines for geometric design features and application of TCDs to deter WW entry at the exit ramp terminals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations